Electroinduced viscosity-reducing glue as well as preparation method and application thereof
By adopting specific formula electroporating adhesives, using conductive agents and alkenyl ionic liquids to form an efficient conductive network, the existing electroporating adhesives have been solved, and the problems of poor electroporating effect and low shear strength of existing electroporating adhesives have been solved, achieving high efficiency The peeling and shearing properties are suitable for applications in a variety of electronic fields.
Patent Information
- Application Number
- CN202510019006.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrolytic viscosity reducing adhesives have poor electrolytic effect and low shear strength, which affects the utilization and protection of electronic devices.
Using polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, hydroxylated carbon nanotubes, alkenyl ionic liquids, lithium salts, tackifiers, and dispersants. The electroreductive adhesive composed of initiators and other components forms an efficient conductive network to improve peel strength and shear strength through specific formulations and preparation methods.
It achieves excellent peeling strength and shear strength of electroporating adhesive, high efficiency of reducing viscosity on electricity, no residual glue phenomenon, can be reused, and is suitable for electronic components, connection line fixation and protection.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and more specifically to an electrically induced viscosity-reducing adhesive and a preparation method and application thereof. Background Art
[0002] Traditional tapes rely on UV irradiation or heat treatment to change the bonding strength of the adhesive, but these methods have certain limitations, especially for non-transparent parts that cannot be exposed to UV light or parts with poor heat resistance. Electro-debonding tape combines electrical and bonding technologies to achieve controllable peeling between the tape and the bonding surface by applying voltage. When an external voltage is applied to the electro-debonding adhesive, the electric field can guide the polar molecules in the adhesive to rearrange, thereby reducing its adhesion to the contact surface, allowing the tape to be easily peeled without the need for UV irradiation or high-temperature heating. Therefore, electro-debonding tape not only improves the flexibility of the bonding process, but also broadens its application range in electronics, automotive, medical and consumer electronics.
[0003] At present, CN115895519A discloses an electrolytic adhesive and a double-sided tape, wherein the electrolytic adhesive comprises the following raw material components by weight: 100 parts of an adhesive body, 5-30 parts of a solid conductive salt, and 5-50 parts of a polar aprotic solvent, wherein the solid conductive salt is used to provide anions, and the solid conductive salt is at least one of an ammonium salt, a halogenated carbonate, and an organic sulfonate containing an alkali metal; the polar aprotic solvent comprises dimethyl carbonate and propylene carbonate; anions and cations in the electrolytic adhesive are easily precipitated, which easily leads to poor electrolytic bonding effect and low shear strength of the adhesive, thereby affecting the utilization and protection of electronic devices.
[0004] Based on the above statements, the present invention proposes an electro-viscosity reducing adhesive and a preparation method and application thereof. Summary of the invention
[0005] In order to solve the problems of poor electrolytic adhesiveness and low shear strength of the existing electrolytic viscosity-reducing adhesive, the present invention provides an electrolytic viscosity-reducing adhesive and a preparation method thereof.
[0006] In the first aspect, the present invention provides an electro-induced viscosity-reducing adhesive, which adopts the following technical solution: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100-150 parts of polyacrylate, 30-50 parts of polyvinyl alcohol, 20-40 parts of functional monomer, 1-5 parts of conductive agent, 2-6 parts of olefin-containing ionic liquid, 1-5 parts of lithium salt, 1-5 parts of tackifier, 1-2 parts of dispersant, 0.1-2 parts of initiator, and 60-100 parts of organic solvent; The conductive agent is obtained by modifying hydroxylated carbon nanotubes in a coordinated manner with 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid.
[0007] Preferably, the functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5-8:3.
[0008] Preferably, the conductive agent is prepared by the following method: The hydroxylated carbon nanotubes are ultrasonically dispersed in chloroform, and then 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid are added, mixed evenly, stirred and reacted at 55-65° C. for 1-3 hours. After the reaction is completed, the conductive agent is filtered, washed and dried to obtain the conductive agent.
[0009] Preferably, the ratio of the amount of the hydroxylated carbon nanotubes, 2-thiophenecarboxylic acid, 2-pyridinecarboxylic acid and chloroform is 10 g: 1 g: 0.6-1 g: 100-150 mL.
[0010] Preferably, the alkenyl-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt and / or 1-allyl-3-vinylimidazole dinitrile amine salt.
[0011] Preferably, the alkenyl-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:3.
[0012] Preferably, the lithium salt is two or more of lithium acrylate, lithium itaconate, lithium oleate, lithium bis(oxalatoborate) and lithium tetrafluoroborate.
[0013] Preferably, the tackifier is one or more of rosin glycerol ester, rosin pentaerythritol ester, hydrogenated rosin ester, and disproportionated rosin ester.
[0014] Preferably, the dispersant is polyvinyl pyrrolidone or alkyl glycoside.
[0015] Preferably, the initiator is one or more of dodecyl peroxide, dibenzoyl peroxide, tert-butyl pervalerate, dihydroxy cyclohexane peroxide, isopropylbenzene hydroperoxide, azobisisobutyronitrile and azobisisoheptylonitrile.
[0016] Preferably, the organic solvent is one or more of ethylene carbonate, isopropyl alcohol, xylene, ethyl acetate, butyl acetate, and propylene glycol methyl ether acetate.
[0017] In a second aspect, the present invention provides a method for preparing an electro-viscosity reducing adhesive, using the following technical solution: A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40-50°C for 1-2h, heated to 60-80°C, added with initiator, reacted for 3-6h, cooled to room temperature to obtain the electro-induced viscosity-reducing adhesive.
[0018] In a third aspect, the present invention provides an application of an electro-induced viscosity-reducing adhesive, using the following technical solution: An electro-induced viscosity-reducing adhesive is used in an electro-induced viscosity-reducing adhesive tape.
[0019] Preferably, the electro-induced anti-adhesion tape is prepared by the following method: The electrolytic viscosity-reducing adhesive is coated on the release film A, and the release film B is composited after drying, and then rolled up to complete the aging.
[0020] Preferably, the release films A and B are made of polyethylene, polypropylene or polyethylene terephthalate.
[0021] In summary, the present invention has the following beneficial effects: 1. The raw materials of the electro-viscosity reducing adhesive of the present invention include polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefin-containing ionic liquid, lithium salt, thickener, and dispersant. The components interact with each other, effectively avoiding a large amount of precipitation of electrolyte when electricity is applied. The obtained electro-viscosity reducing adhesive has excellent peel strength and shear strength, high efficiency of electricity-induced viscosity reduction, no residual adhesive phenomenon, and can be reused. It can be widely used in the fixation and protection of electronic components and connecting lines.
[0022] 2. The conductive agent of the present invention is obtained by synergistically modifying hydroxylated carbon nanotubes with 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid; both 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid molecules contain electron-rich aromatic heterocyclic rings that can form π-π conjugated bonds with carbon atoms of carbon nanotubes, which is conducive to the transfer of charge and enhances the electron transfer efficiency of carbon nanotubes; and 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid molecules jointly modify carbon nanotubes, the structure of thiophene ring plus pyridine ring, the spatial distribution ratio of carbon, nitrogen and sulfur atoms is different, and the electronegativity of nitrogen atoms and sulfur atoms is stronger than that of carbon atoms, so that there is a significant difference in electron cloud density, forming holes, and further increasing the migration efficiency of carriers; at the same time, the two improve the dispersibility of carbon nanotubes, improve the interface contact between carbon nanotubes and other components, and help to form an efficient conductive network inside the colloid. The conductive agent of the present invention not only promotes the easy peeling of the electro-viscosity-reducing adhesive at low voltage by applying a short voltage, but also enhances the shear strength of the electro-viscosity-reducing adhesive.
[0023] 3. The alkenyl-containing ionic liquid of the present invention is 1-vinyl-3-methylimidazole dinitrile amine salt and / or 1-allyl-3-vinylimidazole dinitrile amine salt. Both cations and anions of the two can participate in the copolymerization reaction, avoiding the phenomenon that anions and cations are easily precipitated, enhancing the cohesive force of the colloid, and the addition of the alkenyl-containing ionic liquid, in coordination with the conductive agent, has a better viscosity-reducing effect after power-on, and has a better viscosity-reducing effect after power-on, and it is not easy to leave residual glue on the surface during peeling; the present invention further preferably uses a mixture of 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a specific mass ratio as the alkenyl-containing ionic liquid, and the two synergize to increase the crosslinking density inside the colloid, make the intermolecular bonding closer, form a more complex network structure, thereby obtaining more ion transmission channels, and improving the overall performance of the electro-induced viscosity-reducing adhesive.
[0024] 4. The preparation method of the electro-viscosity reducing adhesive of the present invention has simple steps and low cost. In the preparation process, various process parameters are controlled to promote the interaction between various raw materials, so that high-performance electro-viscosity reducing adhesive can be obtained, which can be widely used in electro-viscosity reducing tapes. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below with reference to the embodiments.
[0026] The materials and reagents used in the present invention, unless otherwise specified, can be obtained from commercial sources; among them, hydroxylated carbon nanotubes, CAS No. 1333-86-4, item No. 100226, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. (purity 60%, diameter 2-4nm, hydroxylation content 2.92wt%); polyacrylate is polyacrylate-2, CAS No. 31759-42-9, purchased from Jinjinle Chemical Co., Ltd.; polyvinyl alcohol, CAS No. 9002-89-5, Mw 13000-23000, 98% hydrolyzed, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 1-ethylene 1-allyl-3-vinylimidazole dinitrile amine salt, CAS No. 1416358-78-5, purity 98%, purchased from Qingdao Aolike New Material Technology Co., Ltd.; 1-allyl-3-vinylimidazole dinitrile amine salt, CAS No. 1072788-95-4, purity 98%, purchased from Qingdao Aolike New Material Technology Co., Ltd.; polyvinylpyrrolidone, PVPK90, CAS No. 9003-39-8, industrial grade 20%, purchased from Huzhou Shenhua Polymer Materials Co., Ltd.; alkyl glycoside, APG1214, CAS No. 157707-88-5, purchased from Hubei Zhongnuoyaxing Biotechnology Co., Ltd.
[0027] Preparation Example 1-3 and Comparative Preparation Example 1-2 provide a method for preparing a conductive agent.
[0028] Preparation Example 1: The conductive agent is prepared by the following method: 10 g of hydroxylated carbon nanotubes are ultrasonically dispersed in 100 mL of chloroform, and then 1 g of 2-thiophenecarboxylic acid and 0.6 g of 2-pyridinecarboxylic acid are added, mixed evenly, stirred and reacted at 55° C. for 3 h. After the reaction is completed, the conductive agent is filtered, washed, and dried to obtain the conductive agent.
[0029] Preparation Example 2: The conductive agent is prepared by the following method: 10 g of hydroxylated carbon nanotubes are ultrasonically dispersed in 120 mL of chloroform, and then 1 g of 2-thiophenecarboxylic acid and 0.8 g of 2-pyridinecarboxylic acid are added, mixed evenly, stirred and reacted at 60° C. for 2 h. After the reaction is completed, the conductive agent is filtered, washed, and dried to obtain the conductive agent.
[0030] Preparation Example 3: The conductive agent is prepared by the following method: 10 g of hydroxylated carbon nanotubes are ultrasonically dispersed in 150 mL of chloroform, 1 g of 2-thiophenecarboxylic acid and 1 g of 2-pyridinecarboxylic acid are added, the mixture is evenly mixed, and the mixture is stirred and reacted at 65° C. for 1 h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the conductive agent.
[0031] Comparative Preparation Example 1: Comparative Preparation Example 1, the difference from Preparation Example 1 is that an equal mass of 2-thiophenecarboxylic acid is used to replace 2-pyridinecarboxylic acid, as follows: The conductive agent is prepared by the following method: 10 g of hydroxylated carbon nanotubes are ultrasonically dispersed in 100 mL of chloroform, 1.6 g of 2-thiophenecarboxylic acid is added, the mixture is evenly mixed, and the mixture is stirred at 55° C. for 3 h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the conductive agent.
[0032] Comparative Preparation Example 2: Comparative Preparation Example 2 is different from Preparation Example 1 in that an equal amount of 2-pyridinecarboxylic acid is used to replace 2-thiophenecarboxylic acid, as follows: Conductive agent, prepared by the following method: 10 g of hydroxylated carbon nanotubes were ultrasonically dispersed in 100 mL of chloroform, and 1.6 g of 2-pyridinecarboxylic acid was added and mixed evenly. The mixture was stirred and reacted at 55° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a conductive agent.
[0033] Embodiment 1-6 provides an electro-viscosity reducing adhesive and a preparation method thereof.
[0034] Embodiment 1:
[0035] An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the olefin-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0036] Embodiment 2:
[0037] An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 120 parts of polyacrylate, 40 parts of polyvinyl alcohol, 30 parts of functional monomer, 5 parts of conductive agent, 4 parts of olefin-containing ionic liquid, 3 parts of lithium salt, 3 parts of tackifier, 1.5 parts of dispersant, 0.5 parts of initiator, and 80 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:7:3; the conductive agent is prepared by Preparation Example 2; the alkenyl-containing ionic liquid is 1-allyl-3-vinyl imidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium itaconate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is hydrogenated rosin ester; the dispersant is alkyl glycoside; the initiator is tert-butyl peroxypentylaric acid ester; the organic solvent is obtained by mixing isopropanol and propylene glycol methyl ether acetate in a mass ratio of 1:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 45°C for 1.5 hours, heated to 70°C, added with initiator, reacted for 4.5 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0038] Embodiment 3:
[0039] An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 150 parts of polyacrylate, 50 parts of polyvinyl alcohol, 40 parts of functional monomer, 1 part of conductive agent, 6 parts of olefin-containing ionic liquid, 5 parts of lithium salt, 5 parts of tackifier, 2 parts of dispersant, 2 parts of initiator, and 100 parts of organic solvent; Among them, the functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:8:3; the conductive agent is prepared by Preparation Example 3; the olefin-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:5; the lithium salt is obtained by mixing lithium oleate and lithium bis(oxalatoborate) in a mass ratio of 1:1; the tackifier is rosin pentaerythritol ester; the dispersant is polyvinylpyrrolidone; the initiator is obtained by mixing dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:1; the organic solvent is obtained by mixing ethylene carbonate and xylene in a mass ratio of 1:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 50°C for 1 hour, heated to 80°C, added with initiator, reacted for 3 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0040] Embodiment 4:
[0041] Example 4 is different from Example 1 only in that the alkenyl-containing ionic liquid is 1-allyl-3-vinyl imidazole dinitrile amine salt, specifically as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the alkenyl-containing ionic liquid is 1-allyl-3-vinyl imidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0042] Embodiment 5:
[0043] Example 5 is different from Example 1 only in that the alkenyl-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:1, as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the olefin-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:1; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0044] Embodiment 6:
[0045] Example 6 is different from Example 1 only in that the alkenyl-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:3, as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the olefin-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:3; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0046] In order to verify the performance of the electro-viscosity reducing adhesives obtained in Examples 1-6 of the present invention, the present invention sets up Comparative Examples 1-6.
[0047] Comparative Example 1: Comparative Example 1 is different from Example 1 only in that the conductive agent is prepared by Comparative Preparation Example 1, which is as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by comparative preparation example 1; the olefin-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0048] Comparative Example 2: Comparative Example 2 is different from Example 1 only in that the conductive agent is prepared by Comparative Preparation Example 2, which is as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by comparative preparation example 2; the olefin-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0049] Comparative Example 3: Comparative Example 3 is different from Example 1 only in that the conductive agent is hydroxylated carbon nanotubes, specifically as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is hydroxylated carbon nanotubes; the olefin-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0050] Comparative Example 4: Comparative Example 4 is different from Example 1 only in that the alkenyl-containing ionic liquid is 1-allyl-3-butylimidazole bistrifluoromethanesulfonyl imide salt, specifically as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 2 parts of conductive agent, 2 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the alkenyl-containing ionic liquid is 1-allyl-3-butylimidazole bistrifluoromethanesulfonyl imide salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0051] Comparative Example 5: Comparative Example 5 is different from Example 1 only in that an equal mass of conductive agent is used to replace the alkenyl-containing ionic liquid, as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 4 parts of conductive agent, 1 part of lithium salt, 1 part of thickener, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the conductive agent is prepared by Preparation Example 1; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, lithium salt, thickener and dispersant are added to the organic solvent, mixed evenly, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0052] Comparative Example 6: Comparative Example 6 is different from Example 1 only in that an equal mass of olefin-containing ionic liquid is used to replace the conductive agent, as follows: An electro-viscosity reducing adhesive comprises the following raw materials in parts by weight: 100 parts of polyacrylate, 30 parts of polyvinyl alcohol, 20 parts of functional monomer, 4 parts of olefin-containing ionic liquid, 1 part of lithium salt, 1 part of tackifier, 1 part of dispersant, 0.1 part of initiator, and 60 parts of organic solvent; The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5:3; the olefin-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt; the lithium salt is obtained by mixing lithium acrylate and lithium tetrafluoroborate in a mass ratio of 1:1; the tackifier is rosin glycerol ester; the dispersant is polyvinyl pyrrolidone; the initiator is dodecyl peroxide; the organic solvent is obtained by mixing ethylene carbonate and ethyl acetate in a mass ratio of 5:1; A method for preparing an electrolytic viscosity-reducing adhesive comprises the following steps: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40°C for 2 hours, heated to 60°C, added with initiator, reacted for 6 hours, cooled to room temperature, and obtained the electro-induced viscosity-reducing adhesive.
[0053] Performance testing: The electrolytic adhesive obtained in Examples 1-6 of the present invention and Comparative Examples 1-6 was coated on release film A (polyethylene), and then composited with release film B (polyethylene) after drying, and then rolled up and aged to obtain an electrolytic adhesive tape; the electrolytic adhesive tape was tested for performance, and the results are shown in Table 1: Refer to GB / T 1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials" to test the surface resistance of the electro-adhesive tape; Refer to GB / T 33332-2016 "Test method for dynamic shear strength of adhesive tape" to test the shear strength of electro-adhesive tape; Refer to GB / T 2792-2014 "Test method for peel strength of adhesive tape" to test the peel strength of the electro-induced adhesive tape before power-on, after power-on and after being placed at room temperature for 24 hours after power-on. The peel strength before power-on is recorded as F1, the peel strength after power-on is recorded as F2, and the peel strength after being placed at room temperature for 24 hours after power-on is recorded as F3; and the recovery rate of the peel strength is calculated as W = (F3 / F1) × 100%.
[0054] Residue test on steel plate surface after power-on stripping: Observe whether there is residual glue on the surface of the steel plate for stripping force test after power-on.
[0055] It can be seen from the data shown in Table 1 above that the comprehensive performance of the electro-induced anti-viscosity tape obtained in Examples 1-6 is significantly better than that of Comparative Examples 1-6. The electro-induced anti-viscosity tape has high adhesion before power-on and ultra-low viscosity after power-on. It can be firmly adhered to the substrate and easily peeled off after power-on without residual glue. The recovery rate of the peel strength after power-on is high, and it can be reused, which has broad application prospects.
[0056] By comparing Example 1 with Comparative Example 3, it can be seen that the conductive agent of the present invention is significantly better than hydroxylated carbon nanotubes and can greatly improve the comprehensive performance of the tape; further comparing Example 1 with Comparative Examples 1-2, it can be seen that the conductive agent of the present invention is obtained by synergistically modifying hydroxylated carbon nanotubes with 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid. The two interact with each other and can significantly enhance the peel strength of the tape before power is applied, reduce the peel strength of the tape after power is applied, and have an excellent electro-induced viscosity reduction effect.
[0057] By comparing Examples 1, 4-6 and Comparative Example 4, it can be seen that the preferred olefin-containing ionic liquid of the present invention helps to improve the peel strength and shear strength of the tape, and has a higher efficiency in reducing viscosity by electrification.
[0058] It can be seen from Example 1 and Comparative Examples 5 and 6 that the conductive agent of the present invention interacts with the alkenyl-containing ionic liquid to form a variety of ion transmission channels, reduce the resistance of carrier migration under the action of the electric field, and achieve an efficient debonding effect under the action of the electric field.
[0059] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. An electro-viscosity reducing adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of polyacrylate, 30-50 parts of polyvinyl alcohol, 20-40 parts of functional monomer, 1-5 parts of conductive agent, 2-6 parts of olefin-containing ionic liquid, 1-5 parts of lithium salt, 1-5 parts of thickener, 1-2 parts of dispersant, 0.1-2 parts of initiator and 60-100 parts of organic solvent; The conductive agent is obtained by modifying hydroxylated carbon nanotubes in a coordinated manner with 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid.
2. The electrolytic viscosity reducing adhesive according to claim 1, characterized in that: The functional monomer is obtained by mixing octadecyl acrylate, 4-vinylbenzoic acid and N-acryloylmorpholine in a mass ratio of 1:5-8:
3.
3. The electrolytic viscosity reducing adhesive according to claim 1, characterized in that: The conductive agent is prepared by the following method: The hydroxylated carbon nanotubes are ultrasonically dispersed in chloroform, and then 2-thiophenecarboxylic acid and 2-pyridinecarboxylic acid are added, mixed evenly, stirred and reacted at 55-65° C. for 1-3 hours. After the reaction is completed, the conductive agent is filtered, washed and dried to obtain the conductive agent.
4. The electrolytic viscosity reducing adhesive according to claim 3, characterized in that: The usage ratio of the hydroxylated carbon nanotubes, 2-thiophenecarboxylic acid, 2-pyridinecarboxylic acid and chloroform is 10g:1g:0.6-1g:100-150mL.
5. The electrolytic viscosity reducing adhesive according to claim 1, characterized in that: The alkenyl-containing ionic liquid is 1-vinyl-3-methylimidazole dinitrile amine salt and / or 1-allyl-3-vinylimidazole dinitrile amine salt.
6. The electrolytic viscosity reducing adhesive according to claim 5, characterized in that: The alkenyl-containing ionic liquid is obtained by mixing 1-vinyl-3-methylimidazole dinitrile amine salt and 1-allyl-3-vinylimidazole dinitrile amine salt in a mass ratio of 1:
3.
7. The electrolytic viscosity reducing adhesive according to claim 1, characterized in that: The lithium salt is two or more of lithium acrylate, lithium itaconate, lithium oleate, lithium bis(oxalatoborate) and lithium tetrafluoroborate.
8. The electrolytic viscosity reducing adhesive according to claim 1, characterized in that: The tackifier is one or more of rosin glycerol ester, rosin pentaerythritol ester, hydrogenated rosin ester, and disproportionated rosin ester; The dispersant is polyvinyl pyrrolidone or alkyl glycoside.
9. A method for preparing the electro-viscosity reducing adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the formula, polyacrylate, polyvinyl alcohol, functional monomer, conductive agent, olefinic ionic liquid, lithium salt, thickener and dispersant are added to the organic solvent, uniformly mixed, reacted at 40-50°C for 1-2h, heated to 60-80°C, added with initiator, reacted for 3-6h, cooled to room temperature to obtain the electro-induced viscosity-reducing adhesive.
10. The electro-viscosity reducing adhesive according to any one of claims 1 to 8 is used in an electro-viscosity reducing adhesive tape.
Citation Information
Patent Citations
Double-sided adhesive tape for electrolyte-resistant battery and preparation method of double-sided adhesive tape
CN115820143A
Carbon nanotube composite dispersant and carbon nanotube dispersion
CN118145628A
Adhesive capable of being debonded by applying voltage and preparation method of adhesive
CN118853032A
Electrolytic adhesive as well as preparation method and application thereof
CN118853035A
Electrolytic adhesive containing stable polymer and preparation method thereof
CN118956301A
Cited By
High-viscosity power-on viscosity-reducing adhesive tape and preparation method thereof
CN120865809A
Halogen-free flame-retardant power-on viscosity-reducing adhesive tape and preparation method thereof
CN121518056A